(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Abstract: This paper investigates the structural impacts of labor precarization and informality on the Brazilian social security system, with a focus on the General Regime of Social Security (RGPS). It analyzes the proliferation of atypical labor relations—such as outsourcing, gig economy, and false self-employment—resulting from neoliberal flexibilization and the 2017 labor reform. These non-standard forms of employment, often lacking legal recognition and formal registration, directly affect workers’ access to constitutionally guaranteed labor and social security rights, such as retirement, paid leave, and severance funds.